A high‐precision global biostratigraphy of myodocope ostracods for the Silurian upper Wenlock Series and Ludlow Series. (2nd October 2019) - Perrier, Vincent; Williams, Mark; Siveter, David J.; Palmer, Douglas; Steeman, Thomas; Vandenbroucke, Thijs R.A.
Abstract : The wide, trans‐oceanic geographical distribution of myodocope ostracods during the Silurian (especially during the Ludlow and Pridoli epochs), and their widespread preservation in rocks of that age, permits the establishment of a transcontinental biostratigraphy of comparable resolution to coeval graptolite/chitinozoan/conodont biozones. Seven myodocope biozones, extending from the Homerian Stage, upper Wenlock Series Cyrtograptus lundgreni graptolite biozone to the middle part of the Ludfordian Stage of the Ludlow Series, enable a time‐resolution for each biozone of circa 1 million years. These biozones can provide high‐resolution correlation across Europe into Arctic Russia and Central Asia. There is also the potential for a myodocope biostratigraphy applicable from the uppermost Silurian (Pridoli) to the Carboniferous.